IMPROVING STUDENTS’ VOCABULARY THROUGH SPELLING BEE GAME - Esteria Salipadang; Paula Hampp; Fivy A Andries (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
This study looked into whether or not using a spelling bee game may help pupils enhance their vocabulary mastery. The goal of this study is to see if students' vocabulary improved after playing the Spelling Bee Game. The quantitative method is used to conduct this study. This study uses a pre-experimental design with a single group pre test and post test. The subject of this research is first grade of SMP Anugrah Tondano consists of 10 students. The tests are in the forms of arrange random words, multiple choice and connecting pairs. The results of this study reveal that the mean post-test scores are higher (75) than the pre-test scores (46). Based on the findings, it can be stated that using the Spelling Bee Game to boost students' vocabulary is helpful since it stimulates students' learning and spelling of nouns.